Surgical revascularization for stable coronary syndrome: the ISCHEMIA trial versus a single-centre matched population—a real-world analysis of patients undergoing surgical revascularization. (10th February 2022) - De Martino, Andrea; Del Re, Federico; Gregori, Dario; Azzolina, Danila; Pascarella, Clemente; Falcetta, Giosuè; Ravenni, Giacomo; Celiento, Michele; Morganti, Riccardo; Colli, Andrea
Abstract: OBJECTIVES: The aim of this study was to test if the current general practice of surgical revascularization is comparable to the setting of International Study of Comparative Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial and to evaluate the comparative risk of cardiovascular events or death after coronary artery bypass grafting. METHODS: We selected patients undergoing surgical revascularization and matching ISCHEMIA inclusion criteria. Chronic coronary syndrome patients were included if diagnosis of myocardial ischaemia by functional testing and coronary artery disease at angiography were detected. The primary end point was a composite of cardiovascular death, myocardial infarction, rehospitalization for unstable angina, heart failure and resuscitated cardiac arrest. Secondary end points were death by any cause, cardiovascular death, myocardial infarction and rehospitalization. RESULTS: Among 353 patients, the primary outcome occurred in 62 (17.6%) patients. At 6 months, cumulative event-free survival was 97%, at 1 year 96%, at 5 years 89% and at 10 years 80%. Cumulative risk of the primary composite outcome at 5 years was 11%, 18% in the conservative arm of ISCHEMIA and 16% in the revascularization arm of ISCHEMIA ( P < 0.001). Risk of myocardial infarction at 5 years was 7% in surgical patients and 12% and 10% in the conservative and invasive arms of the trial, respectively ( P < 0.001). CONCLUSIONS: Long-term results in surgical patients treated for chronic coronary syndromes showed that ISCHEMIA trial findings are not transferable in a 'real-world' scenario and have not changed previous medical practice. A patient-tailored approach, especially with diabetes and reduced left ventricle function, offers the best results in patients with stable coronary artery disease. Abstract : The goals of myocardial revascularization in patients with chronic coronary syndromes are to improve survival and/or to improve symptoms.